2018
DOI: 10.3889/oamjms.2018.415
|View full text |Cite
|
Sign up to set email alerts
|

Different Materials Used as Denture Retainers and Their Colour Stability

Abstract: BACKGROUND:Retainers are of great importance for the longevity of the prosthetic removable partial denture during various functions especially the esthetic one. The key of successful clasp selection is to select a direct retainer that will control tipping and torquing forces on the abutment teeth, provide retention against reasonable dislodging forces and are compatible with both tooth and tissue contour together with the aesthetic desire of the patient.AIM:This study aims to compare different clasp material t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…In our study, about 72.3% of the dentists did choose a specific material for the construction of RPDs, but 10.7% of the dentists did not. One study in the literature emphasized the choice of material for RPDs such as cobalt chromium, but aesthetics was a major concern [26].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, about 72.3% of the dentists did choose a specific material for the construction of RPDs, but 10.7% of the dentists did not. One study in the literature emphasized the choice of material for RPDs such as cobalt chromium, but aesthetics was a major concern [26].…”
Section: Discussionmentioning
confidence: 99%
“…(3) Prosthodontics (File S1; Table S7) (n = 11) [66,[68][69][70][71][72][73][74][75][76][77]; (4) Maxillofacial prostheses (File S1; Table S8) (n = 14) [78][79][80][81][82][83][84][85][86][87][88][89][90][91];…”
Section: Literature Search and Quality Of The Papersmentioning
confidence: 99%
“…Direct retainers vary in shape, origin and materials according to the suitability and requirement of partially dentate situation. 67 Direct retainers are considered to cause gingival recession and increase caries of abutment teeth. [68][69][70][71][72][73][74] However if retainers are placed according to survey line and well supported by rests, they will not cause any harm to periodontal tissue.…”
Section: Effect Of Components Of Removable Partial Denture On Periodontal Status Of Abutments Direct Retainer Designmentioning
confidence: 99%
“…[68][69][70][71][72][73][74] However if retainers are placed according to survey line and well supported by rests, they will not cause any harm to periodontal tissue. 67,75 Some studies have showed that precision attachments are less damaging to periodontium than the clasp type retainers; this may be due to better vertical loading of abutments teeth. 74,[76][77][78][79] For distal extension bases mesial rest with I bar retainers were proven to be more favorable for longevity of abutment teeth.…”
Section: Effect Of Components Of Removable Partial Denture On Periodontal Status Of Abutments Direct Retainer Designmentioning
confidence: 99%